2016
DOI: 10.4274/jcrpe.3027
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Toxicity in Neonatal Intensive Care Units: Phthalate Exposure in Very Low Birth Weight Infants

Abstract: Objective:To determine exposure to endocrine-disrupting phthalates in preterm infants in neonatal intensive care units (NICU).Methods:Urine samples (n=151) from 36 preterm infants (<32 weeks of gestation and/or <1500 g of birth weight) were collected on the first 3 days of admission to the NICU and biweekly thereafter. Diethylhexyl phthalate contents of indwelling medical devices used in various procedures and the concentrations of phthalate metabolites in the urine samples were analyzed. The relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Urinary levels of 5-OH-MEHP may exceed 0.2 µg/mL, a concentration at which we have demonstrated a TRβ agonist effect that was confirmed in vitro as being partial and has a synergistic effect with T3. The maximum values of 5-OH-MEHP measured in the urine of newborns hospitalized in NICUs range from 0.43 µg/mL to 13.1 µg/mL, i.e., 2 to 65 times higher than the concentration activating thyroid receptors [ 36 , 37 , 38 , 39 , 40 ]. Certain medical procedures, such as extracorporeal circulation (extracorporeal membrane oxygenation, cardiopulmonary bypass), respiratory assistance, and intravenous nutrition are recognized as situations with a high risk of exposure, which can explain the high values in multi-exposed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary levels of 5-OH-MEHP may exceed 0.2 µg/mL, a concentration at which we have demonstrated a TRβ agonist effect that was confirmed in vitro as being partial and has a synergistic effect with T3. The maximum values of 5-OH-MEHP measured in the urine of newborns hospitalized in NICUs range from 0.43 µg/mL to 13.1 µg/mL, i.e., 2 to 65 times higher than the concentration activating thyroid receptors [ 36 , 37 , 38 , 39 , 40 ]. Certain medical procedures, such as extracorporeal circulation (extracorporeal membrane oxygenation, cardiopulmonary bypass), respiratory assistance, and intravenous nutrition are recognized as situations with a high risk of exposure, which can explain the high values in multi-exposed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our study of 104 neonates is the first biomonitoring study assessing this exposure to alternative-to-DEHP plasticizers of neonates hospitalized in NICU. Previous NICU studies were conducted on few patients and were intended only to measure the exposure to DEHP via MD, based on the urinary concentrations of its metabolites [ 16 , 17 , 18 , 19 ]. All the authors demonstrated a correlation between the urinary levels of some DEHP metabolites (MEHP, 5-oxo-MEHP, and 5-OH-MEHP) and the exposure of NICU patients to DEHP via MD, higher than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fetal and neonatal periods are very sensitive periods to the effects of endocrine disruptors. Overall, multiple and intensive medical interventions and an impaired ability to excrete phthalates may explain the susceptibility of neonates, and particularly preterm infants, to high DEHP exposure, the latter being associated with the intensity and duration of invasive medical procedures [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the final product, DEHP can contribute up to 40% of the finished weight of plastic medical products (e.g., intravenous fluid bags, blood storage bags), and up to 80% of the weight of flexible medical tubing (Halden, 2010; Jaeger & Rubin, 1973, 2010; Plonait, Nau, Maier, Wittfoht, & Obladen, 1993). Since phthalates are not covalently bound to PVC, these chemical additives are known to leach or migrate into surrounding solutions, including blood (Table 2) (Barry et al, 1989; D'Alessandro et al, 2019; Demirel et al, 2016; Gaynor et al, 2018; Green et al, 2005; Kaestner et al, 2020; Karle et al, 1997; Mallow & Fox, 2014; Münch et al, 2020; Peck et al, 1979; Rael et al, 2009; Sjöberg, Bondesson, Sedin, & Gustafsson, 1985; Sjoberg et al, 1985; Stroustrup et al, 2018; Su et al, 2012; Takatori et al, 2008; van der Meer et al, 2014). Moreover, DEHP leaching is exacerbated under conditions of prolonged use, mechanical stress, higher temperature and/or in the presence of lipid‐containing fluids.…”
Section: Di‐2‐ethylhexyl Phthalatementioning
confidence: 99%